Supreme Court Reforms: The Challenge of Change - Hunter, Richard J.; Shannon, John H.; Lozada, Hector R (Archives of Business Research, 2024)
This article discusses proposals for “reform” of the United States Supreme Court based on the background and facts of five important and controversial Supreme Court cases dealing with campaign finance, voting rights, abortion rights, the administrative state, and finally, and perhaps most critically, presidential immunity for alleged criminal acts.